2011
DOI: 10.1002/jmv.22137
|View full text |Cite
|
Sign up to set email alerts
|

Genotype diversity of group A rotavirus strains in children with acute diarrhea in urban Burkina Faso, 2008–2010

Abstract: In this study, the diversity of G and P genotypes of rotavirus strains in Burkinabe children were examined. Between November 2008 and February 2010, 447 stool samples were collected from children <5 years of age with acute diarrhea visiting hospital in Ouagadougou. Group A rotavirus was previously detected in 151/447 (33.8%) of the samples tested by an immunochromatographic test and these samples were now tested further for rotavirus G and P genotypes by RT‐PCR. Of these, the rotavirus type genes were ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…The G2 and P[4] types are not present in the monovalent G1P[8] vaccine, and it has been suggested that the vaccine shows a lesser efficiency to this type (Gurgel et al, 2007). During this RVA season however, the G2P[4] RVs were not highly prevalent and a study from Burkina Faso the previous year showed a similar prevalence of G2 strains (Bonkoungou et al, 2011).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The G2 and P[4] types are not present in the monovalent G1P[8] vaccine, and it has been suggested that the vaccine shows a lesser efficiency to this type (Gurgel et al, 2007). During this RVA season however, the G2P[4] RVs were not highly prevalent and a study from Burkina Faso the previous year showed a similar prevalence of G2 strains (Bonkoungou et al, 2011).…”
Section: Discussionmentioning
confidence: 87%
“…In Burkina Faso, previous studies have observed a high burden of RVA disease in children with high RVA prevalence during the cold dry season December-February (Bonkoungou et al, 2010(Bonkoungou et al, , 2011Nitiema et al, 2011;Steele et al, 2010). Furthermore, in a previous study from the capital Ouagadougou, RVA strains were characterized by their G and P-types (Nordgren et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…A prior study analyzing feces from children Ͻ5 years of age with acute diarrhea reported that 34% of them were positive for rotavirus by an immunochromatographic assay (SD Bioline Rota/Adeno; Standard Diagnostics, Inc., Kyonggi-Do, South Korea) (12,13). Samples were collected between November 2008 and February 2010 from the capital city of Ouagadougou in Burkina Faso (12).…”
Section: Methodsmentioning
confidence: 99%
“…Here we report on a viral metagenomic analysis of feces of children from Burkina Faso with acute diarrhea (12) allowing the characterization of their enteric viruses, including the genetic characterization of novel parvoviruses from a previously unrecognized genus (12,13).…”
mentioning
confidence: 99%
“…Moreover, in developing countries, some authors highlight the existence of significant diversity of rotavirus strains with unusual type combinations that could influence RV vaccine effectiveness. 62,63 Recently Gladstone et al showed that early infection and frequent reinfection in a setting with high viral diversity resulted in lower protection than has been reported elsewhere, providing a possible explanation for the observed lower than expected efficacy of rotavirus vaccine in Asia and Africa. 64 …”
Section: Post-licensure Effectivenessmentioning
confidence: 96%